Rheology of aqueous mullite-starch suspensions - Talou, Mariano Hernán (2011)
One of the forming methods developed for the manufacture of porous materials by direct consolidation, in which a ceramic suspension consolidates into non-porous molds (e.g. metal molds) by thermogelation of an organic agent, uses starch as both consolidator/binder of the ceramic suspension and pore former at high temperature. Changes in the rheological behavior of the aqueous suspensions are produced by starch gelatinization thermal process. This process as well as the presence of both the ceramic particles and added processing additives, influences the kinetics of green ceramic body formation and its microstructural features. In this work, the thermogelling behavior of mullite aqueous suspensions (40 vol.%; 0.45 wt.% of a polyacrylic polyelectrolyte as dispersant) containing 10 vol.% of different native starches (potato, cassava, and corn) was studied by dynamic rheology in order to determine the experimental conditions that must be used for forming mullite green bodies by thermal consolidation. Viscoelastic properties (G′ and G″) as a function of temperature (30–95 °C) and deformation (0.1–625.0% at 40 °C) were determined by temperature sweep tests and dynamic strain sweep tests, respectively. From these tests, and considering previous results of the rheological behavior of starch suspensions, we analyzed the influence of ceramic particles on the starch gelatinization process and the strength of the developed gels. On the other hand, shear flow properties of aqueous mullite–starch suspensions were also analyzed to obtain information on the rheological behavior of the suspensions at room temperature.